Overexpression of leucine‐rich repeat‐containing G protein‐coupled receptor 5 in gastric cancer. (16th December 2012) - Yamanoi, Kazuhiro; Fukuma, Mariko; Uchida, Hiroshi; Kushima, Ryoji; Yamazaki, Ken; Katai, Hitoshi; Kanai, Yae; Sakamoto, Michiie
<x xml:space="preserve">Abstract</x> Gastric cancer is one of the most common malignancies worldwide and patients with advanced gastric cancer still have poor clinical outcomes. The overexpression of leucine‐rich repeat‐containing G protein‐coupled receptor 5 (LGR5) mRNA in colorectal cancer and its correlation with clinicopathological factors were recently reported by us. In this study, we show LGR5 mRNA overexpression in human gastric cancer specimens by quantitative RT‐PCR and in situ hybridization and assess a correlation with clinicopathological factors. The mean expression of LGR5 mRNA in cancerous tissues was five times higher than that in normal tissue (P = 0.0002). Furthermore, LGR5 mRNA expression show marked variation among cases and significantly increased in cases where lymphatic invasion was present compared with those where it was absent (P = 0.0056). Although the mean expression level of LGR5 was observed to be higher in nodal metastasis and venous invasion positive cases compared to negative cases, a significant difference was not observed. These results suggest that LGR5 can be a biomarker for malignancy in gastric cancer.